Business Ethics In The Framework Of Corporate Governance: A Literacy Study - Dahminar Iscana Dewi; Setyo Riyanto (Jurnal Indonesia Sosial Teknologi, 2021)
This journal is as a discussion or proof of the implementation of good business ethics in the organization as a bridge to good organizational governance, and corporate values through theories or expert opinions. The existence of good ethics in organizational governance is expected to be a force in the value of the company, and the determination of policy. Business ethics in the framework of corporate governance and corporate values become a great responsibility for the company to its stakeholders. In this case maintain the loyalty of stakeholders in making company decisions and in solving corporate problems. This is because all company decisions are highly influenced and influenced by stakeholders. Forming a company that is strong and has high competitiveness and has the ability to create high corporate value, a solid foundation is required.